Predicting the effects of global warming and extreme climate events on zooplankton functional responses and ecological interactions. - Bomfim, Francieli de Fátima (2020)
Global warming can affect thedistribution and development of organisms indirectly through changes in climate patterns and thus, in the habitat of species and, directly through the influence of high temperatures on the physiological and morphological development of organisms. These changes in thepatterns of species density, feeding and reproduction driven by warming and environmental changes also induce changes in the ecological relationships in which these organisms are involved. Thus, we investigated how these two effects of global warming, affect the performance, distribution and ecological relationships of zooplankton species, using functional responses of the organisms, such as biomass production and functional traits, in order to link these changes in zooplankton with ecosystem services. This studyis divided into three approaches, microcosm experiments controlling three temperatures, predation and competition and, a spatial and temporal approach in the upper Paraná River floodplain. In our experiments, we observed that temperature increases indeed lead to more complex relationships inside food webs, with possible negative consequences for aquatic ecosystems. However, the temperature was not the predominant factor in determining the performance of subtropical and temperate cladoceran species, as predation was the mainly structuring factor, changing the performance and competition among species. The study with the spatial and temporal approach showed that extreme climate events modify the limnological heterogeneity of shallow lakes, consequentlyaltering zooplankton species and functional traits, especially by species and traits substitution among environments (beta replacement). Factors related to predation, food availability, limnological variables and, temporal variations influenced differently the zooplankton functional beta diversity depending on the climatic event and the type of lake (connected or isolated), but limnological variables are in fact the most important factor in structuring the zooplankton distribution. Both warming and changes in climate patterns (especially intense dry seasons) negatively affected zooplankton organisms, reducing biomass production, secondary production and, the richness of functional traits among environments. The reduction of these zooplankton functional variables has negative consequences for energy stocks and, the flow of matter inside aquatic food webs, changing the ecosystem services.